Electromagnetic profiling for groundwater in precambrian basement complex areas of Nigeria (1990)
Ground electromagnetic profiling, using a Geonics EM34-3 instrument, has been employed to identify areas of high conductivity in a Precambrian basement complex terrain of Nigeria. Field examples, conducted as part of a rural water supply programme, are presented. They indicate that the apparent conductivities are generally lower than about 60 mmho m-1. Subsequent borehole drilling suggests a good correlation between high EM34 anomalies, deep weathering and high well yield (> 1 1 s-1). On the other hand, boreholes sited on conductivity lows penetrated a thinner regolith with relatively lower yields.